Covid-19 related isolation and risk of post-traumatic stress disorder in patients presenting to tele-clinics at a private tertiary care hospital in Karachi - Syed Faisal Mahmood,; Nasir, Samrah; Amin, Muneeba; Arshad, Aleena; Asad, Nargis; Nadeem, Tania (Journal of the Pakistan Medical Association, 2024)
The objective of this study was to assess the psychological impact of isolation on individuals with Covid-19 and determine the experiences of people in isolation. All adults with Covid-19 who reported to the infectious disease tele-clinic were included in the study; participants were sent the survey form via email. The email was sent to 146 people and 47 responses were received. IES-R questionnaire was submitted to all individuals on Day 7 of quarantine, along with a qualitative questionnaire. The mean score on IES-R for all the respondents was 18.77. Out of 47 participants, for 6 (12.8%) PTSD was a clinical concern, 3 (6.4%) participants had a probable diagnosis of PTSD, and 6 (12.8%) participants scored high enough to suppress immune function. The majority of participants reported stress due to confinement in an isolated space and interruption in daily routine, specifically work-related routine. ---Continue